Pengembangan Vidio Animasi Dengan Pendekatan Saintifik Berorientasi Pemecahan Masalah Model Search, Solve, Create, Share Untuk Siswa Kelas V - Pera Natasia; Irwan Koto; Endang Widi Winarni (UNIB Press, 2023)
The purpose of this study is to describe the process of creating an animated video and determine its feasibility based on the results of the validator's assessment and student responses using a scientific approach geared toward solving the problem of the Search, Solve, Create, Share model for class V students. Procedure research and development refers to the Borg and Gall development model, which has ten stages, but only seven are used by researchers, namely up to the use trial and then product revision if there are validator suggestions. The study's findings were based on the validator's assessment of the material aspect, which received an average score of 0.81, the language aspect, which received an average score of 0.83, and the media aspect, which received an average score of 0.80. The overall average of these three aspects yields a score of 0.81 in the very decent category, while the results of student responses yield an average score of 80.5 in the very good category. Based on the assessment results, it can be stated that the developed learning media in the form of animated videos is very feasible and suitable for use in the learning process.